2015
DOI: 10.1016/j.cmi.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Immune-driven adaptation of hepatitis B virus genotype D involves preferential alteration in B-cell epitopes and replicative attenuation—an insight from human immunodeficiency virus/hepatitis B virus coinfection

Abstract: An important driving force behind the sequence diversity of hepatitis B virus (HBV) is viral adaptation to host immune responses. To gain an insight into the impact of host immunity on genetic diversification and properties of HBV, we characterized HBV of genotype D from treatment-naive hepatitis B e antigen-positive (EP) and hepatitis B e antigen-negative (EN) patients with chronic hepatitis B (CHB), where HBV is under stronger immune pressure, with that of HBV derived from human immunodeficiency virus (HIV)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…The location of mutations that are associated with HBV-related disease progression are variable; Kim et al ( 2012 ) found that such core protein mutations were primarily located within CD4 + T-cell epitopes that were designated MHC class II restricted regions (Kim et al, 2012 ), while Carman et al ( 1997 ) found that HBcAg mutations associated with progressive disease were concentrated in B-cell epitopes (Carman et al, 1997 ). A separate study of Indian patients infected with HBV genotype D identified advantageous mutations in B-cell epitopes during the progression of chronic hepatitis B infection (Mondal et al, 2015 ). Similarly, Assar et al ( 2012 ) reported several mutations responsible for immune evasion in T helper and B-cell epitopes in Iranian patients infected with HBV genotype D (Assar et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The location of mutations that are associated with HBV-related disease progression are variable; Kim et al ( 2012 ) found that such core protein mutations were primarily located within CD4 + T-cell epitopes that were designated MHC class II restricted regions (Kim et al, 2012 ), while Carman et al ( 1997 ) found that HBcAg mutations associated with progressive disease were concentrated in B-cell epitopes (Carman et al, 1997 ). A separate study of Indian patients infected with HBV genotype D identified advantageous mutations in B-cell epitopes during the progression of chronic hepatitis B infection (Mondal et al, 2015 ). Similarly, Assar et al ( 2012 ) reported several mutations responsible for immune evasion in T helper and B-cell epitopes in Iranian patients infected with HBV genotype D (Assar et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro replication assay depicted a significant reduction in the replication efficiency of HBV in presence of these rt and rh mutations, which could partly explain the low copy numbers of HBV in OBI-positive patients. Further, the slow replication rates are often advantageous for viruses as by generating fewer virus-derived peptides, they could avoid being eliminated by host immune system and thereby have a greater likelihood of persistence in the host 34 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the genetic affiliation of OHBV strains, the full-length sequences obtained in the study were compared with representative sequences of ten HBV genotypes (A–J) retrieved from GenBank. Alignments were carried out using CLUSTALX software and a phylogenetic tree was constructed by the neighbour joining (NJ) method using the Jukes–Cantor model in MEGA software version 6 34 . To identify the potential mutations in HBV that are associated with occult status, the complete sequences of OHBV belonging to genotype D (OHBV/D) were compared with 167 HBV/D sequences derived from HBsAg-positive carriers that comprised of 62 sequences from Eastern India (EI) and 105 sequences from other geographical locations (WRLD), all of which are available in GenBank.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations